DEVELOPMENT OF CREATIVE ABILITIES OF STUDENTS BASED ON EDUCATION OF THE ABILITY TO SCIENTIFIC GENERALIZATION (Web of Teachers: Inderscience Research, 2023)
The article discusses the development of students' creative abilities based on cultivating the ability to scientific generalization.